Barriers, enablers and motivators of the “I’m an active Hero” physical activity intervention for preschool children: a qualitative study - Al-walah, Mosfer A.; Donnelly, Michael; Heron, Neil (Frontiers in Pediatrics, 2024)
Background: Insufficient physical activity (PA) in early childhood is linked to adverse health outcomes and a heightened risk of an increased prevalence of obesity. Successful PA programmes often require tend to re-quire input from key stakeholders, such as parents and educators. However, research on stakeholders' perspectives regarding PA programmes for preschool children is limited, impeding effective programme design and implementation.Objectives: This study aims aimed to explore the perspectives of key stakeholders to gain insights into the challengesobtain insights into the obstacles, facilitators, and motivators that influence influencing the planning, execution, and sustainability of the 'I'm an Active Hero (IAAH) intervention component,' a preschool-based initiative designed to promote PA among young children.Methods: Semi-structured interviews were conducted in Saudi Arabia with individual preschool principals (n = 2), and focus group discussions were held, respectively, with preschool staff members (n = 4, all female) and parents (4 mothers, 5 fathers).Results: A thematic analysis identified four main themes:of the data revealed four central themes: 1) Barriers to parental involvement in-volvement in preschool PA interventions, such as time constraints, lack of flexibilityinflexibility, limitedinadequate space, and a shortage of a dearth of trained staff; 2) Risks and benefits of children's programme participation; 3) Motivators including encompassing rewards, non-financial incentives, and concerns about childhood obesity and a sedentary lifestyle; 4) Facilitating factors Facilitative factors for overcoming barriers, including such as staff training, time reallocation, staff coordination, space space optimization adjustments, non-financial incentives, and sustaining partnerships.This study's findings are crucial The findings of this study hold great significance for childcare professionals, preschools, education authorities, and policymakers, offering valuable insights for future researchcontributing valuable insights to existing research. However, further collaboration